Enhancing alfalfa yield via micro-nano bubble oxygenation in subsurface drip irrigation: rhizosphere mechanisms unveiled by structural equation modeling - Cao, Xuesong; Zheng, Hexiang; Wang, Yuxiang; Geng, Wei; Zi, Qianqian; Feng, Yaxing (Frontiers in Plant Science, 2025)
Water scarcity and soil hypoxia are major constraints to forage productivity in arid regions. This study investigated the effects of subsurface drip irrigation with micro-nano bubble oxygenated water (MNBO) on the rhizosphere environment, root physiology, growth, and quality of alfalfa (Medicago sativa L. cv. ‘Caoyuan No. 2’) under field conditions in Inner Mongolia. A full factorial experimental design was employed, combining three irrigation levels (20, 25, and 30 mm) and three dissolved oxygen concentrations (1.8, 5.0, and 8.2 mg/L). Structural equation modeling (SEM) was applied to quantify the direct and indirect effects of irrigation and oxygenation on yield formation pathways. Results demonstrated that MNBO irrigation significantly improved soil enzyme activities (catalase by 15–28%; urease by 18–32%), microbial abundance (bacteria, fungi, actinomycetes), and root vitality (27.9–103.6%), thereby promoting plant growth and yield. The optimal treatment (25 mm irrigation with 5.0 mg/L DO) increased dry matter yield by 8.3–30.1%, crude protein by 11.2–11.5%, and crude fat by 18.8–27.6% compared to conventional practices. Structural equation modeling revealed that yield improvement was primarily mediated through enhanced soil biological activity and root functionality, rather than direct irrigation effects. These findings provide a scientifically robust irrigation strategy that synergistically enhances water use efficiency and root zone aeration, offering significant potential to support sustainable forage production in water-limited ecosystems.